Chemical tuning of Coulomb blockade at room-temperature in ultra-small platinum nanoparticle self-assemblies. Issue 3 (6th April 2017) - Tricard, Simon; Said-Aizpuru, Olivier; Bouzouita, Donia; Usmani, Suhail; Gillet, Angélique; Tassé, Marine; Poteau, Romuald; Viau, Guillaume; Demont, Phillipe; Carrey, Julian; Chaudret, Bruno
Abstract : Self-assembly is a first step towards nanoelectronic systems, where the charging energy of ultra-small nanoparticles is tuned by the nature of the ligands. Abstract : This work describes self-assemblies of ultra-small platinum nanoparticles, the electrical properties of which can be adjusted through slight modifications of the assemblies' constituents. Elaborating such systems, stable in air for months, is a first step towards nanoelectronic systems, where the charging energy of the nanoparticles is tuned by the nature of the ligands.